Machka lizhe kontakt . Cat Licks a Contact… - Stoyanov, Nikola (Napredak, 2003)
A creative AIDS-awareness cartoon ("Anti-AIDS Propaganda according to the subtitle), which interprets the concept of safe sex quite literally.